2004
DOI: 10.1111/j.1365-2273.2004.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucociliary clearance after external dacryocystorhinostomy

Abstract: We investigated the nasal mucociliary clearance time in 17 patients who underwent a primary unilateral external dacryocystorhinostomy operation. Mucociliary clearance function in both nasal cavities was assessed with the saccharin test. The results were compared with each other using paired samples t-test. We found significantly worse mucociliary clearance time on the operated side (mean: 6.3 min) than on the non-operated side (mean: 5.5 min) (P = 0.004). External dacryocystorhinostomy negatively affected the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…Mucociliary clearance is an important component of the defence mechanisms of the respiratory tracts and can be impaired by conditions such as CRS 19 that affect the activity of cilia. Diminished mucociliary clearance has also been reported following both external 20 and EnDCR. 21,22 Saline nasal irrigation is therefore recommended for secondary prevention of CRS, recurrent ARS, and after sinus surgery.…”
Section: Discussionmentioning
confidence: 93%
“…Mucociliary clearance is an important component of the defence mechanisms of the respiratory tracts and can be impaired by conditions such as CRS 19 that affect the activity of cilia. Diminished mucociliary clearance has also been reported following both external 20 and EnDCR. 21,22 Saline nasal irrigation is therefore recommended for secondary prevention of CRS, recurrent ARS, and after sinus surgery.…”
Section: Discussionmentioning
confidence: 93%
“…The pretest guidance found in the literature includes not ingesting alcoholic or caffeine-based substances, such as coffee, tea, soda, and energy drinks; drugs such as anesthetics, analgesics, barbiturates, tranquilizers, and antidepressants; not smoking for at least 12 hours; and not performing vigorous physical activities during the 12 hours preceding the test. 22 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54…”
Section: Review Of a Particular Subjectmentioning
confidence: 99%
“…Gudis et al, carried out an updated literature review of cilia dysfunction in CRS which concluded that patients with CRS had a reduction of the mucociliary clearance 8. Moreover, other studies have reported this reduction after EDCR and EnDCR 911…”
Section: Discussionmentioning
confidence: 99%